Using the UTAUT Model to Determine the Factors Affecting the Technology Acceptance in Judicial System Environment - Amrouni, Khaled I. A.; Ruzaini, Abdullah Arshah (Penerbit Akademia Baru, 2018)
The implementation of e-government technology to support both user and organization enables both to perform better by facilitating and decision-making processes. This paper addresses the problem of how to determine the factors that influence employees to accept and use technology implemented in Judicial System institutions in developing countries focusing on acceptance technology theories. The research model employed in this study is based on the Unified Theory of Acceptance and Use of Technology (UTAUT). The study will be undertaken via quantitative method by distributing questionnaires to target respondents. The intended method of data analysis describes the objectives to be included later, including a variable analysis followed by the intended quantitative analysis. Finally, the expected outcome of this study is to identify the possible issues which occur when implementing e-government in a local law environment.